Policing in 21st Century - Case Study of Islamabad Safe City Authority - Joya, Muhammad Haroon; Bashir, Khalida (Journal of Pakistan Administration, 2019)
The rise of urban population warrants a paradigm shift in security assurance strategies. Safe city projects have been a novel approach comprising of state-of-the-art technologies aimed at aiding government and law enforcement authorities to come up with rapid response to threats. The solutions primarily consist of sensor technologies acquiring constant data followed by the analysis of the data through rigorous and robust mechanisms enabling the deterrence of crime leading to overall prosperity for the population. Albeit the technical research on safe city projects and its components has been commonplace there is still a dearth of viable research for assessing the performance of the projects in its intended purposes. Moreover, little research is conducted on the secondary benefits of such projects. This research endeavors to analyze the case study of Islamabad Safe City Project through primary and secondary data to answer two basic question: Has Islamabad Safe City Project resulted in crime reduction? And has the Islamabad Safe City Project resulted in improvement in the quality of life of the residents of Islamabad? On the first question the project has been found lacking as per the analysis of the crime data of the past four years. Crime analysis depicts an immediate drop in crime rates followed by a rise beyond the initial levels. This pattern of crime is seen for all types of crime, thus validating the theory that crime control goes beyond the deterrence strategies and is affected by other socio-economic factors as well. In second part of the research, primary data collected through surveys was utilized to assess the perception of the residents regarding the safe city project. Barring the reduced sense of privacy of the residents, the project seems to have improved all other facets of the lives of the residents pertaining to security.
Keywords: Safe City Authority; 21st Century; Case Study; Islamabad